Experimental study of an optical concentrated solar thermoelectric power generator - Sameer Ali Alsibiani (Ain Shams Engineering Journal, 2024)
The commercial thermoelectric modules become more and more efficient in terms of mechanical reliability, cooling capacity (in Peltier mode), power generation (in Seebeck mode), tolerable thermal conditions and so on. In this paper a portable optical concentrated solar thermoelectric generator is proposed, designed, tested, and evaluated based on a single UTX15-288-F2 module in both transient and steady-state conditions. A 30 cm diameter optical concentrator is employed to concentrate the solar power on one side of thermoelectric. Due to the low scale of the generated power, the active cooling methods for the other side of the module is not desirable and economical. That is why the boundary condition of the other low temperature side of thermoelectric is just natural convection by a heatsink under shadow condition. The aim of this case study is to clarify the UTX15-288-F2 module behavior under the mentioned conditions for possible portable micropower applications. Generated power, solar radiation, temperature of both side of the module and ambient conditions are measured during the experiments, reported, discussed, and analyzed.